Evaluation of the Growth of Black Mangrove (Avicennia germinans) Established in Plantations on a Technosol Soil (Agro Productividad, 2025)
Objective:To evaluate the growth of black mangrove (Avicennia germinans L.) in a nine-hectare plantation located in the Ejido La Solución Somos Todos, Paraíso, Tabasco, by assessing the height and diameter of plants established on Tecnosol soils.Design/Methodology/Approach: The plantation was established at a density of 625 plants per hectare. A Completely Randomized Design (CRD) was employed across three plots exhibiting similar edaphic characteristics. In each plot, 69 plants were randomly selected for monitoring. Measurements were conducted six months after planting using a graduated wooden ruler for height and a vernier caliper for diameter. ANOVA was applied to evaluate significant differences between plots, followed by Tukey’s test for multiple comparisons. Results: revealed statistically significant differences in plant growth. Plot 3 recorded the highest average height (75.08 ± 14.3 cm), while Plot 2 showed the greatest average diameter (0.46 ± 0.272 cm). In contrast, Plot 1 exhibited the lowest growth performance (45.33 ± 16.6 cm). These differences were directly associated with site quality despite the common use of landfill soils, certain areas offered more favorable conditions than others. The observed variation underscores the complexity of environmental dynamics influencing mangrove development.Study Limitations/Implications: A key limitation of this study lies in the influence of uncontrolled external factors, emphasizing the need for ongoing, long-term monitoring. Findings/Conclusions: Black mangrove growth is highly dependent on soil characteristics, moisture levels, solar radiation, and salinity.